Aerodynamic characteristics of a high-speed train exposed to heavy rain environment based on non-spherical raindrop. Issue 211 (April 2021) - Yu, Mengge; Liu, Jiali; Dai, Zhiyuan
Abstract: The aerodynamic characteristics of high-speed trains operating in severe environment have gained an increasing interest in the past few years. As rain is a common weather phenomenon, understanding its effects on the aerodynamic characteristics of the high-speed train provides valuable information for the design of a train. In the present paper, the aerodynamic model of a high-speed train operating in a dry condition is first set up, and the simulation results are compared with the existing wind tunnel test data to validate accuracy of the mesh resolution and CFD technique. For the simulation of raindrops, the applicability of spherical raindrop assumption in numerical simulations is discussed in this paper. The results demonstrate that, when the equivalent spherical diameters are greater than 2 ​mm, the simulation errors of terminal velocity of raindrops exceed 3%. The non-spherical characteristics of raindrops need to be considered for large particle sizes, and the particle sphericity for various equivalent spherical diameters is investigated. After that, a two-way coupled Euler-Lagrange approach is developed to evaluate the aerodynamic characteristics of a high-speed train in heavy rain environment based on non-spherical raindrop assumption. The flow around the train, pressure coefficient distribution, skin friction coefficient distribution, and aerodynamic force coefficients of the high-speed train exposed to heavy rain environment are then investigated. It is found that the aerodynamic coefficients of the high-speed train increase approximately linearly with the rainfall intensity. The explicit equations for predicting the aerodynamic force coefficient which is correlated with train speed and rainfall intensity are proposed in this study. Highlights: The aerodynamic effect of heavy rain on the high-speed train is investigated using Euler-Lagrange approach. The non-spherical characteristics of raindrops need to be considered for large raindrop sizes. The aerodynamic coefficients of the high-speed train increase approximately linearly with the rainfall intensity. The explicit equation of the aerodynamic force coefficient correlated with train speed and rainfall intensity is proposed.